Shear Modulus Imaging with Spatially Modulated Ultrasound Radiation Force - McAleavey, Stephen (2009)
The application of Spatially Modulated Ultrasound Radiation Force (SMURF) to shear modulus imaging is demonstrated in tissue mimicking phantoms and porcine liver. Scanning and data acquisition was performed with a Siemens Antares ultrasound scanner and VF7-3 linear array operating at 4.21 MHz. Modulus estimates in uniform phantoms of Zerdine(™) with shear moduli of 5.1 and 12.4 kPa exhibited standard deviations within 6% of the mean value. Zerdine spheres 1 cm in diameter (nominally 2.7, 4.7, and 15 kPa) in a 8 kPa (nominal) background are clearly resolved. Cross sectional images of a soft conical inclusion in a gelatin-based phantom indicate a spatial resolution of approximately 2.5 mm. Images of the shear modulus of an ex-vivo sample of porcine liver tissue show an average value of 3kPa. A stiff lesion induced with 0.5 mL of 10% glutaraldehyde is clearly visible as a region of shear modulus in excess of 10 kPa. A modulus gradient associated with the diffusion of the glutaraldehyde is visible. Two pulse sequences were examined, differing only in the timing of the beams used to generate the shear waves. Details of the beam sequences and subsequent signal processing are presented.